A cream of herbal mixture to improve melasma - Zhang, Qiongyu; Tu, Ying; Gu, Hua; Sun, Dongjie; Wu, Wenjuan; Man, Mao‐Qiang; Chen, Hongduo; Liu, Haiyang; Ma, Xiao; He, Li (Journal of cosmetic dermatology, 2019)
Summary Background Melasma is an acquired, common hyperpigmented disorder on the face. While many therapeutic approaches are available, their efficacy is moderate. Objective To investigate the safety and efficacy of a cream containing herbal mixture for melasma. Methods A total of 90 volunteers with melasma were enrolled in this randomized, double‐blind, controlled clinical study, and they were randomly divided into three groups (A, B, and C). Patients in group A were treated with a cream containing herbal mixture, while groups B and C were treated with arbutin cream and placebo, respectively, twice daily for 12 weeks. Melasma area and severity index (MASI) score, melanin index (MI), erythema index (EI), changes in density of inflammatory cells, and adverse events were evaluated every 4 weeks. Results Although MASI scores declined significantly in both groups A and B (P < 0.05), a greater reduction was seen in group A (13.00−9.82 = 3.18 for group A; 12.65−10.84 = 1.81 for group B). Moreover, the cream containing herbal mixture, but not arbutin cream and placebo, significantly reduced EI and density of inflammatory cells after 12‐week treatment (P < 0.05). No adverse reactions were observed in either group A or group C. In group B, two subjects experienced mild erythema and itching, which disappeared after stop using the arbutin cream. Conclusion The cream containing herbal mixture is safe and effective for melasma.